In vitro and in vivo assessment of free radical scavenging and antioxidant activities of Veronica persica Poir - Sharifi-Rad, Javad; Sharifi-Rad, Mehdi; Salehi, Bahare; Iriti, Marcello; Roointan, Amir; Mnayer, Dima; Soltani-Nejad, Azam; Afshari, Azam (Cellular and Molecular Biology, 2018)
With the appearance of new disorders along with inability of some conventional therapies for the treatment of diseases without any side effects, the discovery of safe and efficient therapeutic agents is of utmost importance in the medical area. In this context, medicinal plants as promising therapeutic candidates can provide a reliable and efficient profile. Since free radicals are at the center of various disorder pathways, reducing their production or complete removal of these chemical species could be advantageous for prevention and treatment of many diseases. In this experiment, free radical scavenging and antioxidant activities of Veronica persica Poir., a known medicinal plant, were evaluated using in vitro and in vivo assays. Chemical characterization results showed a high phenolic content in the V. persica methanol extract. In addition, in vitro assays including DPPH radical-scavenging assay, nitric oxide-scavenging activity assay, hydrogen peroxide scavenging test and bleomycin-dependent DNA damage test revealed significant antioxidant power and radical scavenging capacity of this plant. In accordance, in vivo experiments showed inhibitory effects of the methanol extract on lipid peroxidation, a main cause of cell damage. Our findings revealed the promising potential of this plant in reducing free radicals through different pathways. Moreover, our data suggested a correlation between the high phenolic content of the V. persica extract and its free radical scavenging and antioxidant activities.